Daya Pembengkakan (Swelling Power) Campuran Tepung Kimpul (Xanthosoma sagittifolium) dan Tepung Terigu Terhadap Tingkat Pengembangan dan Kesukaan Sensorik Roti Tawar - Hidayati, Farida Umi Nur; , Rusdin Rauf, S.TP., M.P; , Dwi Sarbini, S.ST., M.Kes (2013)
Swelling power is the power flour to inflate, influenced by many factors such as amylase, amylopectin and temperature. One of the factors that influence the expansion levels of bread is a swelling power. This research aims to know influence of swelling power ratio of mixture of Xanthosoma sagittifolium flour and wheat flour toward the expansion levels and sensory preferences of bread. Type of research is experimental research. The research design used was completely randomized design group with the various 4 treatments of Xanthosoma sagittifolium flour. The data ratio mixture of flour to the swelling power, the expansion levels and sensory preferences of bread analyzed using one-way ANOVA test.